2011
DOI: 10.1161/strokeaha.110.597799
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte Colony-Stimulating Factor Enhances Arteriogenesis and Ameliorates Cerebral Damage in a Mouse Model of Ischemic Stroke

Abstract: Background and Purpose-Enhancing collateral artery growth is a potent therapeutic approach to treat cardiovascular ischemic disease from occlusive artery. Granulocyte-macrophage colony-stimulating factor (GM-CSF) has gained attention for its ability to promote arteriogenesis, ameliorating brain damage, by the mechanisms involving monocyte upregulation. However, the recent clinical study testing its efficacy in myocardial ischemia has raised the question about its safety. We tested alternative colony-stimulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 29 publications
5
57
2
1
Order By: Relevance
“…G-CSF is a glycoprotein originally found to be involved in the proliferation, survival, and maturation of granulocytes but later shown to confer neuroprotection against ischemic insult by directly binding its corresponding receptor to neurons (Schabitz et al, 2003). G-CSF and its receptor have been shown to be induced upon brain ischemia in the peri-ischemic area (Schneider et al, 2005), and G-CSF has been suggested to serve as a defense mechanism against ischemic cell death by multiple mechanisms (Sugiyama et al, 2011;Solaroglu et al, 2009). Even though the AXIS-2 clinical trial for G-CSF treatment failed to show efficacy in humans, the mechanisms by which G-CSF could mediate neuroprotection in elderly patients with comorbidities with elevated systemic inflammatory burden have not been modeled in preclinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…G-CSF is a glycoprotein originally found to be involved in the proliferation, survival, and maturation of granulocytes but later shown to confer neuroprotection against ischemic insult by directly binding its corresponding receptor to neurons (Schabitz et al, 2003). G-CSF and its receptor have been shown to be induced upon brain ischemia in the peri-ischemic area (Schneider et al, 2005), and G-CSF has been suggested to serve as a defense mechanism against ischemic cell death by multiple mechanisms (Sugiyama et al, 2011;Solaroglu et al, 2009). Even though the AXIS-2 clinical trial for G-CSF treatment failed to show efficacy in humans, the mechanisms by which G-CSF could mediate neuroprotection in elderly patients with comorbidities with elevated systemic inflammatory burden have not been modeled in preclinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although perfusion of latex has originally been carried out through the ascending aorta 2,3 , alternative routes of perfusion are also reported including the left ventricle 7,8 or the common carotid artery 9 . We found no significant difference in the outcomes following perfusion through either the ascending aorta or the left ventricle (unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic injection of GM-CSF in rats for 6 weeks prior to bilateral common carotid artery occlusion has been shown to attenuate functional impairment of cerebrovascular reserve capacity and increase leptomeningeal collateral density (Schneider et al, 2007). A recent study demonstrated that five days of daily GM-CSF or G-CSF administered to C57/BL6 mice after unilateral occlusion of the common carotid artery also promoted leptomeningeal collateral growth and decreased infarct volume (Sugiyama et al, 2011). A subset of these animals received MCAo seven days after common carotid occlusion.…”
Section: Angiogenesis and Collateralsmentioning
confidence: 99%
“…While mild induced hypertension may be neuroprotective, it is important to note that chronic hypertension worsens stroke outcome (Aslanyan et al, 2003;Geeganage et al, 2011;Toyoda et al, 2009), possibly due to inhibition of collateral blood flow. In spontaneously hypertensive rats, compensatory growth of leptomeningeal collaterals in response to chronic cerebral hypoperfusion is impaired relative to normotensive rats, though this compensatory growth is restored by anti-hypertensive therapies (Omura-Matsuoka et al, 2011). Clinically, blood pressure is often elevated during MCAo and clinical trials have not demonstrated unequivocal beneficial results in neurological outcome after stroke (Liebeskind, 2003).…”
Section: Augmenting Cerebral Blood Flow By Inducing Mild Hypertensionmentioning
confidence: 99%